Relationship between hand grip strength and nutritional assessment methods used of hospitalized patients - Garcia,Monique Ferreira (2013)
OBJECTIVE: This study verified the association between hand grip strength and body mass index, subjective global assessment and nutritional risk screening 2002. METHODS: This cross-sectional study calculated the body mass index, measured hand grip strength and administered the subjective global assessment and nutritional risk screening 2002 to 118 patients hospitalized at the University Hospital of the Universidade Federal de Santa Catarina, Florianópolis, Brazil. Hand grip strength was compared with the reference values for the Brazilian population according to gender and age. The statistical analyses included the Student's t-test or Mann-Whitney test and multiple linear regression. The results were considered significant when p<0.05. RESULTS: The prevalences of nutritional risk or malnutrition according to body mass index, global subjective assessment, nutritional risk screening 2002 and hand grip strength were 3.5%, 50.9%, 33.9% and 35.6%, respectively. Malnourished individuals according to body mass index had, on average, 11.0kg less hand grip strength than the nourished individuals (p=0.008). There was no association between hand grip strength and the subjective global assessment (malnourished individuals had -2.8kg; p=0.078) and nutritional risk screening 2002 (malnourished individuals had -1.5kg; p=0.352). CONCLUSION: Hand grip strength was associated with body mass index but not with the subjective global assessment or nutritional risk screening 2002.